Rethinking the presentation at Olduvai Gorge site museum within Integrated Landscape Management (ILM) framework - Luiz Oosterbeek, Everlyne E. Mbwambo (Africana Studia, 2020)
Despite the relevance of the Olduvai complex and of the remarkable research undertaken for decades, the picture that one gets from the current site museum display is that of the incomplete and fragmented representation of Olduvai Gorge cultural landscape. Noticeable, there are aspects and themes of presentation and interpretation at the site museum which have remained largely unchanged despite the ever changing and dynamic cultural landscape and knowledge resulting from research. This paper raises issues of comprehensive integrated presentation of all themes represented in the territory framed in the broader perspective of heritage management within integrated landscape management framework. The paper opined that 21st century museums (OG site museum) need to take into consideration the presentation of all territorial themes that incorporate tangible and intangible heritage visible or not on the cultural landscape. In the end the paper recommends rethinking presentation by modelling integrated preservation and presentation strategies that ensure the message of the past and present are interpreted and presented effectively to the indigenous communities as well as the visitors for sustainable heritage management. Key-words: Olduvai Gorge – Tanzânia – Masai –Gestão Integrada do Território